Phraseological units with the semantics of “evil” in Russian and Kyrgyz languages - A. K. Orozova (Неофилология, 2025)
INTRODUCTION. The basic ethical idea of evil, which comes into opposition with good, is noted in human communities in different historical eras and in different cultures, which is reflected in such a linguistic unit as phraseology, which takes place in the vocabulary of a native speaker of any language. The purpose of the study is to present the results of a comparative analysis of Russian and Kyrgyz phraseological units with semantics of “evil”, to reveal the national and cultural specifics of the concept “evil” as an ethnically significant idea of the moral character of a person.MATERIALS AND METHODS. The research material is lexicographic sources and a card index compiled by the author based on observations of spontaneous speech and phrase use in live speech of speakers of Russian and Kyrgyz languages. Methods of continuous sampling of factual material, definition, and comparison are used; The main method is descriptive and analytical.RESULTS AND DISCUSSION. An analysis of the phraseological units of the Russian and Kyrgyz languages with the semantics of ruthlessness, cruelty and malice showed that they reflect not only the emotional aspects of human nature, but also the characteristics of cultures. The Kyrgyz language makes extensive use of artifacts such as “sword”, “whip”, “blood”, and “poison”, which convey complex human feelings and moral vices. To express negative qualities, somatic phraseological units are used; in the Russian language, phraseological units with zoonims predominate, objectifying the national traits themselves and linguistic and cultural significance. Phraseologisms with the semantics of the image of an evil person in the compared languages are characterized by a metaphorical component that reflects the nationally specific nature of native speakers.CONCLUSION. The analysis of phraseological units with the meaning of “evil” in Russian and Kyrgyz languages has revealed the influence of cultural characteristics on their semantics, imagery, and structure, reflecting the specifics of perceiving negative traits in each culture. The results of the study emphasize the importance of examining phraseological units to gain a deeper understanding of the historical and social experience of peoples, their mentality, and values. A promising direction for further research is the expansion of comparative analysis to include other languages and cultures in order to explore the universal and unique aspects of the perception of evil.